Proteomic Investigation Reveals Eukaryotic Translation Initiation Factor 5A Involvement in Porcine Reproductive and Respiratory Syndrome Virus Infection in vitro - Li, Huawei; Wan, Bo; Jiang, Dawei; Ji, Pengchao; Zhao, Mengmeng; Li, Xinfeng; Li, Rui; Qiao, Songlin (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most critical animal pathogens in the world and causes enormous losses in global swine industry. An in-depth investigation of PRRSV-host interaction will be beneficial for preventing and control of the virus. In this study, we performed a label-free quantitative proteomic assay to analyze the dynamic proteomics of porcine alveolar macrophages (PAMs) infected by highly pathogenic PRRSV strain HN07-1, and identified 269 significantly differentially expressed host cellular proteins. Among them, the protein abundance of eukaryotic translation initiation factor (eIF) family members was revealed to be reduced in PRRSV-infected PAMs. Furthermore, knockdown of eIF5A was demonstrated to remarkably suppress PRRSV proliferation and progeny viral titers in vitro. These results showed the importance of eIF5A in PRRSV infection and its down-regulation as an antiviral strategy by host cells. The current study deepens our understanding of PRRSV pathogenesis and provides novel insights to develop effective strategies against the virus.